How can NGO interventions break the poverty trap? Evidence from at-risk youths in the Philippines. Issue 5 (4th July 2022) - Hirai, Hanayo; Hiyane, Akira
ABSTRACT: This article identifies factors of NGO interventions that enable an escape from the poverty trap, through in-depth analysis of the life courses of at-risk youths engaged with an NGO in the Philippines slums. Applying the Trajectory Equifinality Model for interview analysis, the study found the following crucial factors: a mentor role based on continuous support between youths and NGO staff; comprehensive intervention for children, family, and community focusing on children's career and life planning; peer educators; and transitional work opportunities. The findings demonstrate lessons for the development community in policy formulation and the implementation of programmes to effectively tackle child poverty.